EVALUATION OF THE CORRELATION BETWEEN THE BASELINE PERFUSION INDEX AND THE INCIDENCE OF HYPOTENSION IN PATIENTS UNDERGOING LOWER ABDOMINAL SURGERY UNDER SUBARACHNOID BLOCK– A PROSPECTIVE OBSERVATIONAL COMPARATIVE COHORT STUDY - Dr. Rashmijit Behera; Dr. Akshaya A (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Hypotension is a common complication following spinal anesthesia during lower abdominal surgeries. The perfusion index (PI), a non-invasive measure of peripheral vascular tone, may serve as a predictor for the development of hypotension after spinal anesthesia. Aim: To evaluate the correlation between baseline perfusion index and the incidence of hypotension in patients undergoing lower abdominal surgery under subarachnoid block. Methods: A prospective observational comparative cohort study was conducted on 60 patients undergoing lower abdominal surgery under spinal anesthesia. Patients were divided into two groups based on baseline PI: Group A (PI ≤ 3.5) and Group B (PI > 3.5). Incidence of hypotension, blood pressure trends, and changes in PI after mephentermine administration were recorded and analyzed. Results: The incidence of hypotension was significantly higher in Group B (30%) compared to Group A (6.66%). Group B showed greater decreases in systolic, diastolic, and mean arterial blood pressures post-spinal anesthesia. The baseline PI cutoff value of >3.5 predicted hypotension with a sensitivity of 81.82% and specificity of 53.06%. PI significantly decreased after administration of mephentermine, indicating increased vascular tone. Conclusion: Baseline perfusion index is a useful, non-invasive predictor of hypotension in patients undergoing lower abdominal surgery under spinal anesthesia. Patients with PI > 3.5 are at higher risk of hypotension and may benefit from closer hemodynamic monitoring and early intervention.